PATH PLANNING AND OBSTACLE AVOIDANCE METHODS FOR AUTONOMOUS MOBILE ROBOTS - Ihor Berizka (Електроніка та інформаційні технології, 2024)
Navigation and path planning are among the central problems in the development of mobile and autonomous robots. Research in this field has been conducted for decades, and several methodologies have been proposed to solve these problems. In the field, these approaches are divided into classical or deterministic and non-deterministic or heuristic methods. The article provides a brief overview of typical representatives of both classes, as well as an extended review of methods based on artificial potential fields.